Cytokine profile of pediatric patients with obsessive-compulsive and/or movement disorder symptoms: A review - Fabricius, Rebecca Alison; Sørensen, Camilla Birgitte; Skov, Liselotte; Debes, Nanette Mol (Frontiers in Pediatrics, 2022)
Cytokines are an important modulator of the immune system and have been found to be altered significantly in many neurological and psychiatric disorders, like obsessive compulsive disorder (OCD) and movement disorders. Also, in pediatric autoimmune neuropsychiatric disorders associated with group A streptococcal infections (PANDAS), which are characterized by abrupt debut of symptoms of OCD and /or movement disorder symptoms, alterations in the immune system have been suggested. The aim of this paper was to review the current literature on the cytokine profile of pediatric patients with symptoms of OCD and/or movement disorder symptoms. A search of PubMed and Medline was performed with specific keywords to review studies measuring cytokines in pediatric patients with symptoms of OCD and/or movement disorders. Nineteen studies were found, twelve of which included a healthy control group, while four studies had control groups of children with other disorders, primarily neurological or psychiatric. One study compared cytokines measurements to reference intervals, and two studies had a longitudinal design. Many cytokines were found to have significant changes in patients with symptoms of OCD and/or movement disorders compared to both healthy controls and other control groups. Furthermore, differences were found when comparing cytokines in periods of exacerbation with periods of remission of symptoms in study participants. The cytokines that most studies with healthy control groups found to be significantly altered were TNF-α, IL-1β and IL-17. Although the exact role of these cytokines in OCD and movement disorder symptoms remains unclear, the available literature suggests a proinflammatory cytokine profile. This offers interesting perspectives on the pathogenesis of OCD and/or movement disorder symptoms in children, and further research into the implications of cytokines in neuropsychiatric disorders is warranted.